Characterization and application of dolomite rock in Perlis - Salleh, Mohd. Nazry; Kasim, Farizul Hafiz; Ismail, Khairul Nizar; Ghazali, Che Mohd. Ruzaidi; Saad, Saiful Azhar; Daud, Suhardy (2006)
Dolomite which is known by the local as ‘batu reput’, is a primary sediment mineral and abundantly found in Perlis. Perlis is one of the major producers of dolomite in Malaysia that contain large deposit of high-purity dolomite [CaMg(CO3)2]. Pure samples of dolomite recently explored in the Koperasi Rimba Mas Padang Besar Quarry were investigated for their physical, chemical and mineralogical composition. The dolomite, was also thermally treated up to 800ºC to decompose the carbonate bonding. SEM with EDS (Energy Dispersive Spectroscopy), XRF and XRD analysis method were applied in this study.